Performance Evaluation of a Downlink NOMA Based Full-Duplex MAC Protocol in a WLAN System with Variable MCS Level - Lee, Won Jae; Kim, Jae Hyun (Journal of Korean Institute of Communications and Information Sciences, 2021)
Full-duplex (FD) and non-orthogonal multiple access (NOMA) are considered in wireless local area network (WLAN) system to increase throughput and spectrum efficiency. In this paper, we propose a medium access control (MAC) protocol applied NOMA and FD in WLAN system. The proposed MAC protocol considers inter-node interference and power allocation coefficient. Thus, when uplink node transmits data to the AP, the AP can transmit data to downlink nodes in the same frequency simultaneously. Simulation results show that the throughput of the proposed MAC protocol is higher than that of conventional MAC protocols.
Keywords: Full-duplex (FD); medium access control (MAC); modulation and coding scheme (MCS); non-orthogonal multiple access (NOMA); wireless local area network (WLAN)